(untitled) (New York, 2006)
The volume provides a critical examination of ideas about everyday creativity, introducing a variety of approaches to its study. It explores an argument that has become influential within English language studies--that speakers and writers routinely use language creatively, and that there is some continuity between such everyday creativity and literary language. Chapters examine poetic language, narrative and performance in everyday conversation, along with a range of written genres, from graffiti and text messages to online chat.
Keywords: English language,English language,Creativity ( Linguistics ),Creation ( Literary, artistic, etc. ),College readers; Style,Social aspects